2012
DOI: 10.1111/j.1365-2133.2011.10729.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte sedimentation rate as an independent prognostic factor in mycosis fungoides

Abstract: ESR has turned out as independent prognostic factor in mycosis fungoides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Some studies reported that these factors were strongly associated with the prognosis of MF, while others reported a limited relationship. Some studies that investigated the superiority of each of these parameters revealed different results [ 7 , 9 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that these factors were strongly associated with the prognosis of MF, while others reported a limited relationship. Some studies that investigated the superiority of each of these parameters revealed different results [ 7 , 9 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Palpation of the liver, spleen, and an assessment of B symptoms (night sweats, fever, weight loss) are also required. Both ESR and CRP should be measured, because elevated values are associated with a poorer prognosis [4]. In addition, a blood count with differential should be obtained, and liver enzymes, creatinine, LDH, and electrolyte levels should be measured.…”
Section: Diagnosismentioning
confidence: 99%
“…28 The obvious correlation between ESR results and inflammation/infection has brought forth studies of diagnostic and predictive value of the test in conditions such as giant cell arteritis, 29 diabetic osteomyelitis, 30 and mycosis fungoides. 31 Another interesting application of the ESR is in providing the patient and/or practitioner reassurance in cases of 'no pathology'. 32 Current Case Applications The current case study provides an excellent opportunity to dissect the value of the ESR in a real-life clinical scenario.…”
Section: Clinical Utilization Of the Esrmentioning
confidence: 99%